2012
DOI: 10.1021/bi300664j
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Functional Characterization of Iron-Bound Forms of Azotobacter vinelandiiNifIscA

Abstract: The ability of Azotobacter vinelandii NifIscA to bind Fe has been investigated to assess the role of Fe-bound forms in NIF-specific Fe-S cluster biogenesis. NifIscA is shown to bind one Fe(III) or one Fe(II) per homodimer and the spectroscopic and redox properties of both the Fe(III)- and Fe(II)-bound forms have been characterized using the UV-visible absorption, CD and VTMCD, EPR, Mössbauer and resonance Raman spectroscopies. The results reveal a rhombic intermediate-spin (S = 3/2) Fe(III) center (E/D = 0.33,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 75 publications
2
48
0
Order By: Relevance
“…Although IscA and its homologs have been characterized previously as alternative scaffold proteins or carriers (15,(37)(38)(39), IscA has a unique and strong iron-binding activity in vitro (40 -44) and in vivo (31) under aerobic conditions. The three invariant cysteine residues (45), and possibly an oxygen ligand (43), are likely involved in iron binding in IscA. Furthermore, the iron center in IscA can be readily mobilized by L-cysteine and transferred for iron-sulfur cluster assembly in vitro under aerobic conditions (43,44,47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although IscA and its homologs have been characterized previously as alternative scaffold proteins or carriers (15,(37)(38)(39), IscA has a unique and strong iron-binding activity in vitro (40 -44) and in vivo (31) under aerobic conditions. The three invariant cysteine residues (45), and possibly an oxygen ligand (43), are likely involved in iron binding in IscA. Furthermore, the iron center in IscA can be readily mobilized by L-cysteine and transferred for iron-sulfur cluster assembly in vitro under aerobic conditions (43,44,47).…”
Section: Discussionmentioning
confidence: 99%
“…The three invariant cysteine residues (45), and possibly an oxygen ligand (43), are likely involved in iron binding in IscA. Furthermore, the iron center in IscA can be readily mobilized by L-cysteine and transferred for iron-sulfur cluster assembly in vitro under aerobic conditions (43,44,47). Recently, we also reported that E. coli IscA has its unique activity to bind copper in vivo and in vitro and that excess copper can compete with iron for the metal binding sites in IscA and block iron-sulfur cluster biogenesis (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different roles have been assigned to the A. vinelandii IscN counterpart, Nif IscA. First, Nif IscA was shown to bind Fe(II) and Fe(III) and to act as an iron donor for Fe-S biosynthesis (37). Second, Nif IscA was proposed to function as an alternate scaffold for Fe-S biosynthesis (38).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2) (78, 80 -82). The two Isa proteins belong to the A-type family of ISC proteins that have been shown to be either homo-or heterodimers, which can coordinate Fe/S clusters and/or mononuclear iron via three conserved cysteine residues (78,(82)(83)(84). In vitro reconstitution of [2Fe-2S] cluster release from Grx5 to a Isa1-Isa2 heterodimer and subsequent DTT-dependent reductive coupling of two [2Fe-2S] clusters to form a [4Fe-4S] cluster have been reported based on NMR and UV-visible studies (Fig.…”
Section: Synthesis and Trafficking Of The [4fe-4s] Cluster In Mitochomentioning
confidence: 99%